2021
DOI: 10.1002/mp.14995
|View full text |Cite
|
Sign up to set email alerts
|

Measurement‐based range evaluation for quality assurance of CBCT‐based dose calculations in adaptive proton therapy

Abstract: In online adaptive radiation therapy, in-room CBCT imaging data lacks the quality and accurate electron density information a planning X-ray computed tomography (CT) scan provides. Therefore, corrections of the in-room images must be performed to enable dose calculation and treatment adaptation. These procedures need to be Accepted ArticleThis article is protected by copyright. All rights reserved evaluated carefully. So far, evaluations are only based on recalculation of the initial treatment plan on the new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…vCTs may fail for entities with significant interfractional anatomical changes. 19 An alternative is the use of scatter correction algorithms (SCA) [19][20][21][22][23][24] that utilize the vCT as a prior. Most of these studies focused on 3D images, and the few that considered 4D images typically used a vCT-based approach and focused on phantom validation.…”
Section: Introductionmentioning
confidence: 99%
“…vCTs may fail for entities with significant interfractional anatomical changes. 19 An alternative is the use of scatter correction algorithms (SCA) [19][20][21][22][23][24] that utilize the vCT as a prior. Most of these studies focused on 3D images, and the few that considered 4D images typically used a vCT-based approach and focused on phantom validation.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have studied proton range by using cone-beam CT (CBCT) imaging of the patient on the couch. [8][9][10] The calculated proton range error for CBCT is high as a result of image quality and scatter 11,12 but can be mitigated by scatter correction 13,14 or generation of a synthetic CT. 15,16 An alternative is the use of proton range change in the CBCT from day 1, because we are more interested in the relative change of the range instead of the exact range itself. Without scatter correction,one phantom study showed that the error of change of the calculated water-equivalent thickness (WET; the surrogate of proton range from daily CBCTs) was within 2 mm per 1 cm of phantom size change.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have studied proton range by using cone‐beam CT (CBCT) imaging of the patient on the couch 8–10 . The calculated proton range error for CBCT is high as a result of image quality and scatter 11,12 but can be mitigated by scatter correction 13,14 or generation of a synthetic CT 15,16 . An alternative is the use of proton range change in the CBCT from day 1, because we are more interested in the relative change of the range instead of the exact range itself.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the conventional CT scan used for initial radiotherapy treatment planning, volumetric on‐board imaging has been integrated into most linear accelerators (linacs) and proton therapy systems to provide image‐guided radiotherapy (IGRT), allowing for pre‐treatment localization, monitoring of anatomical changes, and online plan adaptation. On‐board cone‐beam CT (CBCT), for example, is routinely used for these purposes and has demonstrated utility for daily dose reconstruction 13–15 . While kV imaging systems are widely used in many systems, they can introduce several disadvantages for treatment planning and dose calculation.…”
Section: Introductionmentioning
confidence: 99%
“…Onboard cone-beam CT (CBCT), for example, is routinely used for these purposes and has demonstrated utility for daily dose reconstruction. [13][14][15] While kV imaging systems are widely used in many systems, they can introduce several disadvantages for treatment planning and dose calculation. Onboard kV CBCT imaging requires that additional hardware be integrated into the accelerator, resulting in different imaging and treatment isocenters.…”
Section: Introductionmentioning
confidence: 99%